Does Completion Thyroidectomy Improve the Outcome of Patients with Minimally Invasive Follicular Carcinoma of the Thyroid? - Sugino, Kiminori; Kameyama, Kaori; Nagahama, Mitsuji; Kitagawa, Wataru; Shibuya, Hiroshi; Ohkuwa, Keiko; Uruno, Takashi; Akaishi, Junko; Suzuki, Akifumi; Masaki, Chie; Matsuzu, Ken-ichi; Kawano, Michikazu; et al. (Annals of surgical oncology, 2014)
Background The diagnosis of minimally invasive follicular thyroid carcinoma (MIFTC) is often made histologically after thyroid lobectomy. We attempted to determine whether completion thyroidectomy should be considered necessary for all patients diagnosed with MIFTC after thyroid lobectomy. Methods The subjects of this study were a total of 324 patients who underwent thyroid lobectomy as initial surgery at our institution between 1989 and 2010 and diagnosed histologically as MIFTC. Completion thyroidectomy was performed on 101 patients, and the other 223 patients were followed up without further treatments. Cumulative cause-specific survival (CSS) rates and distant-metastasis-free survival (DMFS) rates were calculated by the Kaplan–Meier method. Differences between groups were analyzed for statistical significance by the log-rank test. Multivariate analysis was performed by using the Cox proportional hazards model. Results During the follow-up period, 39 patients were diagnosed with distant metastasis, and 7 patients died of their disease. Age at the initial surgery was found to be a significant factor related to DMFS in both the univariate and multivariate analysis and to also be related to CSS in the univariate analysis. Completion thyroidectomy did not have a significant effect on DMFS or CSS according to the results of the univariate analysis, but it had significant effect on DMFS according to the results of the multivariate analysis. Conclusions Although we were unable to demonstrate sufficient statistical evidence that completion thyroidectomy improved the outcome of MIFTC patients, it is noteworthy none of the patient who underwent completion thyroidectomy died of the disease.